Estimated global exportations of Zika virus infections via travellers from Brazil from 2014 to 2015 - Quam, Mikkel B.; Wilder-Smith, Annelies (Journal of travel medicine, 2016)
Abstract. The ongoing Zika pandemic in Latin America illustrates a potential source for further globalized spread. Here, we assessed global travel-related Zika
Gesehen am 29.01.2021